2004
DOI: 10.3168/jds.s0022-0302(04)73508-0
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance and Milk Production of Assaf Sheep in an Intensive Management System

Abstract: The Assaf breed of dairy sheep, a stabilized cross of the Awassi and East Friesian breeds, has replaced the Awassi as the breed of choice in its country of origin, Israel, and has spread to other Mediterranean countries. In Israel the Assaf breed is managed under an intensive production system involving weaning lambs at birth, rearing them artificially, and milking ewes after parturition. There are several breeding periods in the year when ewes are mated following hormonally synchronized estrus. Records of 18,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
3
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 25 publications
11
74
3
5
Order By: Relevance
“…On the contrary, it was higher in comparison with Florina (Christodoulou et al, 1997) and Cine Type sheep (Karaca et al, 2000) classified as multipurpose breeds. Daily milk yield of Lacaune, although higher than daily milk yield of Tsigai and Improved Valachian, was lower than daily milk yield of comparable breeds reported in the literature -East Friesian (Hamann et al, 2004), Assaf (Pollot and Gootwine, 2004) and Lacaune (Barillet et al, 2001;Berger, 2004). The lower milk yield of Lacaune kept in Slovakia is probably a result of different feeding level and insufficient adaptability to different management and environmental conditions that do not allow the outstanding genetic potential to be manifested.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…On the contrary, it was higher in comparison with Florina (Christodoulou et al, 1997) and Cine Type sheep (Karaca et al, 2000) classified as multipurpose breeds. Daily milk yield of Lacaune, although higher than daily milk yield of Tsigai and Improved Valachian, was lower than daily milk yield of comparable breeds reported in the literature -East Friesian (Hamann et al, 2004), Assaf (Pollot and Gootwine, 2004) and Lacaune (Barillet et al, 2001;Berger, 2004). The lower milk yield of Lacaune kept in Slovakia is probably a result of different feeding level and insufficient adaptability to different management and environmental conditions that do not allow the outstanding genetic potential to be manifested.…”
Section: Resultsmentioning
confidence: 65%
“…Contrariwise, small differences (only 4% for both breeds) observed when daily milk yields of Tsigai and Improved Valachian ewes were compared with previous analyses based on the test-day approach (Oravcová et al, 2005) indicate that the phenotype selection of the last years (since 2000) was not reflected in higher milk yields. Average daily milk yield of Tsigai and Improved Valachian breeds was much lower than daily milk yield of dairy breeds like East Friesian (Hamann et al, 2004), Assaf (Pollot and Gootwine, 2004), Churra Gonzalo et al, 1994;El-Saied et al, 1998;Fuertes et al, 1998), and also Bovec, Istrian Pramenka (Komprej et al, 2003), Black-Faced and Blond-Faced Latxa (Gabina et al, 1993), and Sfakia (Kominakis et al, 2001). On the contrary, it was higher in comparison with Florina (Christodoulou et al, 1997) and Cine Type sheep (Karaca et al, 2000) classified as multipurpose breeds.…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive study of the Lacaune lactation curve and biological interpretation As previously reported in Lacaune sheep (Hernandez et al, 2011) and Asaff sheep (Pollott and Gootwine, 2004), the mean milk yield per lactation and the length of lactation decreased with lactation number, that is, with the age of the sheep. The decrease between lactations 1 and 2 was slight, but it increased from lactation 2 onward.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them deal with ewes under experimental conditions (Groenewald et al, 1995;Portolano et al, 1996) or management conditions with suckling periods (Ruiz et al, 2000;Oravcová et al, 2006). Not many studies have been conducted under intensive farm conditions (Pollott andGootwine, 2000 and2004).…”
Section: Introductionmentioning
confidence: 99%
“…environmental variable influencing milk yield in both sheep (Pollott and Gootwine, 2004; a long photoperiod (I6 to '' Of light) Hernandez et aZ., 2007) at northern latitudes, established lactation (Dahl et al, 1997) or dry a management strategy for dairy goat documented* day length is a barely investigated. Therefore, the objective of this study was to evaluate the effect of long- …”
Section: Introductionmentioning
confidence: 99%